Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-49314-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation and assessment of an antibiotic-based, aseptic decontamination manufacturing protocol for therapeutic, vacuum-dried human amniotic membrane

Abstract: Amniotic membrane (AM) is used to treat a range of ophthalmic indications but must be presented in a non-contaminated state. AM from elective caesarean sections contains natural microbial contamination, requiring removal during processing protocols. The aim of this study was to assess the ability of antibiotic decontamination of AM, during processing by innovative low-temperature vacuum-drying. Bioburden of caesarean section AM was assessed, and found to be present in low levels. Subsequently, the process for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The literature proves that using nanoparticles with a smaller diameter (< 30 nm) increases the antibacterial activity of AgNPs against K. pneumoniae and S. aureus 27 . Marsit et al, (2019) reported excellent antibacterial activity of dried amniotic membranes loaded with polymyxin B against P. aeruginosa 20 . There could be several possible explanations for our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature proves that using nanoparticles with a smaller diameter (< 30 nm) increases the antibacterial activity of AgNPs against K. pneumoniae and S. aureus 27 . Marsit et al, (2019) reported excellent antibacterial activity of dried amniotic membranes loaded with polymyxin B against P. aeruginosa 20 . There could be several possible explanations for our results.…”
Section: Discussionmentioning
confidence: 99%
“…The stock solutions of colistin and AgNPs were prepared by adding 150 mg of colistin sulfate powder and AgNP powder separately into 100 mL of de-ionized water (20 min of sonication of AgNPs suspension with vortexing repeatedly for 5 days) in screw-capped glass bottles. A volume of 15.6 mL from the respective stock solutions was picked up and then added individually into 50 mL of distilled water in other screw-capped bottles to make 0.468 mg/mL dilutions of colistin and AgNPs for final use 17 , 19 , 20 . The formula used to calculate dilutions of colistin and AgNPs can be found in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, hAM has several limitations. The theoretic possibility of disease transmission, variation of growth factor content depending on the storage method, [22] and donor characteristics, [23] the processing following caesarean section is demanding, particularly to avoid bacterial contamination, [24] and, ultimately, the exact mechanism of action remains unclear [21]. For these reasons, and given the variable quality of this material and its reduced transparency, [18] new studies focused on the investigation of biological and synthetic alternatives.…”
Section: State-of-the-art Corneal Tissue Engineering Strategiesmentioning
confidence: 99%
“…Therefore, many techniques have been developed to preserve most of the biological properties of amniotic membranes by storage techniques and to prevent disease transmission to recipients [ 204 , 205 , 206 ]. In 2021, a cohort study from Queen Victoria Hospital and Maidstone Hospital showed that a dry and stable human amniotic membrane-derived matrix, Omnigen ® using OmniLenz ® (NuVision Therapies, Nottingham, UK), can easily be applied in the clinical setting with biochemical stability and efficiency as a novel tool to treat LSCD [ 207 , 208 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%